Mood differences between the winning and losing team during the final match of Razak Cup hockey competition 2016 - Ismail, M.; Jani, H.; Amer, A. (International Journal of Sports Science, 2017)
The psychology of mood and its connection with athletic performance has gotten broad attention and consideration over the previous years. The aim of this study was to examine the differences of mood between the winning and losing team of hockey players during the final match of Razak Cup competition 2016. Forty male hockey players from Terengganu and PDRM age ranging from 19 to 28 years (M = 23.70, SD= 3.08), with 2 to 4 years of experience had participated in this study. Brunel Mood State (BRUMS) questionnaire was used to measure the level of mood among the players right before the competition. Result showed that there was significant difference of moods (negative and positive) between winning and losing team. Hence, mood was important because it can predict the performance of the athletes. Coaches or sport psychologist should consider psychological skills training approach during practice and competition conditions.